An Analysis of Teaching Behaviours of Preschool Student Teachers in a Laboratory School Setting - A. Manaf, Zulkifli (Universiti Putra Malaysia Press, 1995)
In this study, the rating of nine dimensions of teaching behaviours of 112 preschool student teachers from a previous study was analysed using exploratory factor analysis. The teaching behaviours were observed and recorded using the observer rating scales. A pattern of behaviours was observed. Four latent variables were found to underlie the nine teaching behaviours. These are: (1) facilitating (2) interpersonal (3) interactive and (4) flexible. These latent variables are correlated with each other. Preschool student teachers in the study exhibited these teaching behaviours in their teaching performance in a laboratory school setting. Recommendations for future research to confirm the teaching behaviour model employing confirmatory factor analysis are presented. The findings of this study could hopefully serve as a useful guide for teacher educators in the preparation of preschool and early childhood teachers.